CoviWall, a whole-virion-inactivated B.1.617.2 vaccine candidate, induces potent humoral and Th1 cell response in mice and protects against B.1.617.2 strain challenge in Syrian hamsters - Jyotsna Dandotiya; Neeta Adhikari; Manas Ranjan Tripathy; Manas Ranjan Tripathy; Kamini Jakhar; Sudipta Sonar; Dibya Ranjan Pati; Vibhu Kanchan; Varsha S. Prasad; Jitendra Kumar; Nitesh K. Senapati; Arti Bharmoria; et al. (Frontiers in Immunology)
Rapid development of coronavirus disease 2019 (COVID-19) vaccines and antiviral drugs have significantly reduced morbidity and mortality worldwide. Although most of the vaccines were developed initially with the ancestral Wuhan antigen, here, we report the development and immunological efficacy of a whole-virion–inactivated vaccine candidate (CoviWall) to combat the deadly B.1.617.2 (Delta strain) infection. In the current study, we demonstrate a consistent manufacturing process under Good Manufacturing Practice for the development of CoviWall and its characterization using various analytical methods as per regulatory compliance. In addition, we provide pre-clinical immunogenicity and protective efficacy data of the CoviWall vaccine. All the three test doses (i.e., low dose, mid dose, and high dose) immunized in C57BL/6 mice elicited a high titer of anti–receptor-binding domain antibody and neutralizing antibody response against severe acute respiratory syndrome coronavirus–2 (SARS-CoV-2) after second booster dose. In addition, CoviWall immunization also produced a significant T-cell response in the immunized animals. Our B.1.617.2 strain challenge data in Syrian hamsters indicate that immunized hamsters show attenuated clinical manifestations of COVID-19 with reduced lung viral load. Moreover, assessment of pulmonary histopathology revealed lower cellular injury, inflammation, and pneumonia in the vaccinated hamsters as compared to the unvaccinated animals. Such promising results augur well for the clinical phase I trial of the CoviWall vaccine and further development against contagious SARS-CoV-2 strains in the future.